Peningkatan Hasil Belajar Siswa Menggunakan Model Problem Based Learning pada Materi Fluida - Zunita Nur Chasanah; Kaharuddin Arafah; Anis Nur (Universitas Negeri Makassar, 2024)
This study aims to determine whether the application of the Problem Based Learning learning model can improve student learning outcomes on static fluid material. The type of this research is classroom action research with the research subjects were 32 students of class XI MIPA 1 MAN 1 Gresik in the odd semester 2021/2022. Data collection was carried out using learning outcomes tests and observations. The data collected were analyzed using descriptive statistical analysis and the average score of student learning outcomes in the pre-cycle was 54.6, the first cycle was 72.6, the second cycle was 79.8 and the third cycle was 83.9. Completeness of learning outcomes in the classical pre-cycle 12.5% in the first cycle of 78.1%. In cycle II and cycle III there was an increase of 87.5%, and 100%. From the results of this study, it can be concluded that the implementation of the Problem Based Learning model can improve student learning outcomes.